Methods for assessing manifestations of respiratory failure in patients with laryngeal and tracheal compression syndrome caused by thyroid diseases and cicatricial tracheal stenosis - V.V. Boyko; V.V. Kritsak; A.L. Sochnieva; V.V. Tkachenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Tracheal compression syndrome is one of the most severe complications of thyroid diseases and cicatricial tracheal stenosis, which is accompanied by respiratory failure. To assess the state of external respiratory function, standard research methods are used such as spirography, pneumotachometry, and body plethysmography. Objective criteria for respiratory failure are indicators of changes in blood gas composition and acid-base balance. However, these methods can only be considered as auxiliary in the diagnosis of tracheal stenosis. Methods for assessing the degree of respiratory failure in this severe pathology have not been studied sufficiently. The purpose is to study methods for assessing the manifestations of respiratory failure in patients with laryngeal and tracheal compression syndrome caused by thyroid diseases and cicatricial tracheal stenosis. Materials and methods. The study included 272 patients with laryngeal and tracheal compression stenosis caused by cicatricial tracheal stenosis: 105 with cicatricial tracheal stenosis and 167 with thyroid diseases. All participants were admitted to the clinic as emergencies and operated for urgent indications for tracheal compression syndrome at the V.T. Zaytsev Institute of General and Urgent Surgery of the NAMSU. The study was conducted in 2018–2024. Results. Laryngeal and tracheal stenosis primarily causes changes in the blood gas composition and acid-base balance of varying intensity. A decrease in blood О2 saturation, especially over an extended period, inevitably affects the functioning of organs with high energy consumption. This makes a comprehensive approach to the treatment of such patients obvious. Therapy should be aimed not only at restoring airway patency, but also at supporting the entire body. Conclusions. To increase the effectiveness of surgical and medical rehabilitation of patients with laryngeal and cervical tracheal stenosis, the outlined set of studies is necessary, which will allow substantiating the pathogenetic treatment of such patients.